Near-optimal control of nonlinear systems with simultaneous controlled and random switches. Issue 11 (2019) - Buşoniu, Lucian; Daafouz, Jamal; Morărescu, Irinel-Constantin
Abstract: We consider dual switched systems, in which two switching signals act simultaneously to select the dynamical mode. The first signal is controlled and the second is random, with probabilities that evolve either periodically or as a function of the dwell time. We formalize both cases as Markov decision processes, which allows them to be solved with a simple approximate dynamic programming algorithm. We illustrate the framework in a problem where the random signal is a delay on the control channel that is used to send the controlled signal to the system.